MAHAR DALAM PERKAWINAN (Kajian Singkat Berdasarkan Pragmatisme Hukum Islam) - Ahmatnijar ahmatnijar (Institut agama islam negeri Padangsidimpuan, 2020)
Mahar is an important element in a marriage which is very relevant to be studied in the frame of pragmatism of Islamic law, although there are still differences in understanding about who is required to prepare - not just submit - the dowry because it is not explicitly confirmed by the text of the texts or other regulations. Mahar is the first gift of a prospective husband to a prospective wife, as a start and preparation for habituating the fulfillment of subsequent material obligations. The readiness of the prospective bridegroom to prepare the bride price is an illustration of his readiness in meeting the next needs. Mahar is interpreted as a gift of sacred value and is also useful as a symbol of honesty, a sign of agreement will be able to live and struggle together, respect for the bride, protection and description of responsibilities in marriage, sincerity, reflection of love, and a willingness to live together. With a picture like that, then the dowry determination must be by the prospective bride and groom, who will prepare it is the prospective bridegroom is not charged or assume as the responsibility of parents. This illustrates that the prospective husband through dowry preparation has begun to make plans for building the family economy. With this pattern, brotherhood and solidarity will be stronger, and for the wife's family will increase the sense of security and happiness because their daughters are in the hands of men who are responsible. In other parts need to be absorbed by the message contained in the text of the hadith المهر استحل من فرجها ...